Identification of SPP1 as an Extracellular Matrix Signature for Metastatic Castration-Resistant Prostate Cancer - Pang, Xiaocong; Xie, Ran; Zhang, Zhuo; Liu, Qianxin; Wu, Shiliang; Cui, Yimin (Frontiers in Oncology, 2019)
The main challenge in treating patients with advanced fatal prostate cancer (PCa) is resistance to androgen deprivation therapy (ADT), which can gradually develop into metastatic castration-resistant prostate cancer (mCRPC). However, the pathologic mechanisms of mCRPC are still far from clear. Given the high incidence and mortality associated with mCRPC, understanding the causes and pathogenesis of this condition as well as identifying potential biomarkers are of great importance. In the research reported here, we integrated several gene expression profiles from hormone sensitive prostate cancer (HSPC) and mCRPC datasets to identify differentially expressed genes (DEGs), key biological pathways, and cellular components. We found that extracellular matrix (ECM) genes were significantly enriched, and further filtered them using Pearson correlation analysis and stepwise regression to find ECM signatures to differentiate between the PCa and mCRPC phenotypes. Six ECM signatures were input into naive Bayes, K-nearest neighbor, logistic regression, and random forest classifiers models. Random forest algorithm with the six-gene prognostic signature showed best performance, which had high sensitivity and specificity for HSPC and mCRPC classification. Among the six ECM genes, SPP1 was identified as the key hub signature for PCa metastasis and drug resistance development; we found that SPP1 protein and mRNA levels were significantly up-regulated in mCRPC compared with HSPC in organoid models and could regulate the androgen receptor signaling pathway. Therefore, SPP1 is a potential novel biomarker and therapeutic target for mCRPC. Further understanding of the role of SPP1 in mCRPC development may help to explore better therapeutic strategies for the prevention and management of metastasis and drug resistance.